2020
DOI: 10.3233/jad-190835
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Intraneuronal Aggregation of Amyloid-β in Endosomes, Mitochondria, Autophagosomes, and Lysosomes

Abstract: This work provides new insight into the age-related basis of Alzheimer's disease (AD), the composition of intraneuronal amyloid (iA␤), and the mechanism of an age-related increase in iA␤ in adult AD-model mouse neurons. A new end-specific antibody for A␤ 45 and another for aggregated forms of A␤ provide new insight into the composition of iA␤ and the mechanism of accumulation in old adult neurons from the 3xTg-AD model mouse. iA␤ levels containing aggregates of A␤ 45 increased 30-50-fold in neurons from young … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 79 publications
(154 reference statements)
1
26
0
Order By: Relevance
“…Mitochondria are organelles central to brain energy processes, and altering glucose availability or dysregulating oxidative phosphorylation can have direct effects on neuronal function and cognitive health (Picard and McEwen, 2014;Anderson, 2018). Recent reports have hypothesized that Aβ may initiate mitochondrial dysfunction, and one theory proposes that Aβ raises cytosolic calcium levels, inhibiting oxidative phosphorylation and, therefore, ATP production (Cardoso et al, 2001;Eckert et al, 2010;Spuch et al, 2012;Kaminsky et al, 2015;Brewer et al, 2020). Moreover, mitochondria delivery to needed brain regions is dependent on tau, a protein related to microtubules (Quintanilla et al, 2012;Amadoro et al, 2014).…”
Section: Mitochondrial Dysfunction and Ad Pathologymentioning
confidence: 99%
“…Mitochondria are organelles central to brain energy processes, and altering glucose availability or dysregulating oxidative phosphorylation can have direct effects on neuronal function and cognitive health (Picard and McEwen, 2014;Anderson, 2018). Recent reports have hypothesized that Aβ may initiate mitochondrial dysfunction, and one theory proposes that Aβ raises cytosolic calcium levels, inhibiting oxidative phosphorylation and, therefore, ATP production (Cardoso et al, 2001;Eckert et al, 2010;Spuch et al, 2012;Kaminsky et al, 2015;Brewer et al, 2020). Moreover, mitochondria delivery to needed brain regions is dependent on tau, a protein related to microtubules (Quintanilla et al, 2012;Amadoro et al, 2014).…”
Section: Mitochondrial Dysfunction and Ad Pathologymentioning
confidence: 99%
“…In addition, a part of iAβ may originate from extracellular sources entering the cells by receptor mediated internalization [127]. According to a very recent hypothesis, fast aggregation of long Aβs (43 to 52 AA residues) is the main component of the iAβ assemblies [129]. Subcellularly, the endoplasmic reticulum-intermediate compartment and the endosomal-lysosomal system participate in iAβ generation [130,131].…”
Section: Intracellular Aβ and Extracellular Plaquesmentioning
confidence: 99%
“…Activated microglia also plays an important role in the formation of amyloid plaques [128]. Very recent experimental data have also revealed that aggregated iAβ co-localized mostly with mitochondria and endosomes and much less with lysosomes in a 3xTg mouse model of AD [129]. Overexpression of Aβ and iAβ formation causes different mitochondrial dysfunctions (inner transport, axonal transport of mitochondria, and depletion in the synapses) [133].…”
Section: Intracellular Aβ and Extracellular Plaquesmentioning
confidence: 99%
“…3). When cells grow older and eventually turn into senescent, they accumulate a large amount of damaged and dysfunctional organelles, which have been implicated to play a causal role in the development of various aging diseases such as Alzheimer's disease and lysosomal storage diseases [25,26]. Organelles in PMVs of hUCMSCs are probably intact and functional.…”
Section: Discussionmentioning
confidence: 99%